Pengembangan Media Pembelajaran Kalender Bilangan Berbasis Teknologi pada Materi Bilangan Prima di Sekolah Dasar - Vivi Fadilla; Zetra Hainul Putra; Eddy Noviana (JURNAL PENDIDIKAN MATEMATIKA, 2022)
The purpose of the research was to develop technology based numeric calender learning media on prime numbers in elementary as a support for proper learning. The feasibility of the media in terms of material and media aspects. Feasibility of the material consist of learning and content aspects. While the feasibility of the media includes aspects of display and programming. The method use in this research was 4D through 4 stapes of development; define, design, develop, and disseminate. The media was validated by material and media experts, and the subjects in this research were 9 fourth-graders of SDNelementary 11 Pekanbaru. The results of the content expert validation were 90% and the media expert valiadation was 72%. The results of students’ responses amounted to 87% for small group trials and 91% for large group trials. So that the technology-based numerical calender learning media on prime number material for elementary schools is feasible based on the experts’ judgment and students’ positive responses.